Lemmel syndrome: a rare condition causing cholangitis due to duodenal diverticulum - Chanda, Abhishek; Sarkar, Suman; Hossain, Md Saddam; Sonthalia, Nikhil; Roy, Nirmalya (International Journal of Advances in Medicine, 2023)
Lemmel syndrome, rare condition occurs when there is one or more diverticulum causes cholangitis and obstructive jaundice due to compression of common bile duct (CBD) by mechanical obstruction. And are commonly recognized as an incidental finding at cross-sectional imaging. There may be also added pathophysiologic mechanisms that also contribute to the process to the development of this syndrome like duodenal diverticula leading to sphincter of Oddi dysfunction and pressure compression of CBD by diverticula. Inflammation of these duodenal diverticula is very rare. Patients undergoing routine gastrointestinal tract (upper GI) evaluation, duodenal diverticulum presents up to 27% of patients mostly periampullary diverticulum. There may be multiple diverticula leading to compression of CBD causing cholangitis.